The Effects of Deferred Action for Childhood Arrivals on the Educational Outcomes of Undocumented Students - Amy Hsin; Francesc Ortega (Institute of Labor Economics (IZA), 2017)
Deferred Action for Childhood Arrivals (DACA) is the first large-scale immigration reform to affect undocumented immigrants in the United States in decades and offers eligible undocumented youth temporary relief from deportation and renewable work permits. While DACA has improved the economic conditions and mental health of undocumented immigrants, we do not know how DACA improves the social mobility of undocumented immigrants through its effect on educational attainment. This paper uses administrative data on students attending a large public university to estimate the effect of DACA on undocumented students' educational outcomes. The data are unique because they accurately identify students' legal status, account for individual heterogeneity, and allow separate analysis of students attending community colleges versus baccalaureate-granting, 4-year colleges. Results from difference-in-difference estimates demonstrate that as a temporary work-permit program, DACA incentivizes work over educational investments but that the effect of DACA on educational investments depends on how easily colleges accommodate working students. At 4-year colleges, DACA induces undocumented students to make binary choices between attending school on a full-time basis or dropping out of school to work. At community colleges, undocumented students have the flexibility to simply reduce course work to accommodate increased work hours. Overall, the results suggest that the precarious and temporary nature of DACA creates barriers to educational investments.
Keywords: J15; J24; 330; immigration; undocumented immigration; education; Deferred Action for Childhood Arrivals; natural experiment